Effect of bioaugmented Linz-Donawitz slag and biochar on physiological and yield attributes of wheat (Triticum aestivum) - POOJA, DIVYA; PRASAD, SHIV; SINGH, BHUPINDER; SHRIVASTAVA, MANOJ; BABU, SUBHASH; VASHISTH, ANANTA; C, AVINASH (The Indian Journal of Agricultural Sciences, 2024)
Industrial wastes and agricultural by-products are increasingly used in crop production as supplements along with fertilizers. An experiment was conducted during the winter (rabi) seasons of 2021 and 2022 at the research farm of the ICAR-Indian Agricultural Research Institute, New Delhi to determine the individual and combined effects of bioaugmented Linz-Donawitz (LD) slag and biochar on physiological and yield attributes of wheat (Triticum aestivum L.) variety HD 2967. Bioaugmented products with cow-dung, LD slag and biochar in different combinations were prepared in laboratory scale and applied in crates. All the treatments were applied with 100%RDF except control. Growth parameters such as total leaf area, chlorophyll content, NDVI; and leaf photosynthetic attributes such as net photosynthetic rate, stomatal conductance and transpiration rate were affected by bio-augmentation. Our study reported an increase in total leaf area (18.2–21.3%), chlorophyll content (26.5–31.0%), net photosynthetic rate (93.2%), stomatal conductance (61.3%), transpiration rate (24.7%) in bioaugmented treatments with LD slag and biochar over 100%RDF. A yield increase of 25.6 and 27.1% was found in bioaugmented treatments with a combination of LD slag (2 t/ha) and biochar (1 t/ha) over 100%RDF during 2021 and 2022, respectively. No. of spikes, grains per spike and dry biomass weight were positively influenced by bioaugmentation. The bioaugmented treatments with a combination of LD slag and biochar gave significantly higher grain yield, followed by bioaugmented LD slag compared to bioaugmented biochar alone in the respective application rate of treatments.